Effects of alkylphenols on the biotransformation of diuron and enzymes involved in the synthesis and clearance of sex steroids in juvenile male tilapia (Oreochromus mossambica) - Felício, Andréia A. [UNESP]; Crago, Jordan; Maryoung, Lindley A.; Almeida, Eduardo A. [UNESP]; Schlenk, Daniel (Elsevier, 2016)
Previous studies using in vivo bioassay guided fractionation indicated that the herbicide diuron (3-(3,4-dichlorophenyl)-1,1-dimethylurea) and alkylphenol (AP)-containing surfactants were detected in fractions of extracts that induced the estrogenic biomarker, vitellogenin in fish exposed to surface water extracts from the United States. However, when the compounds were evaluated individually using in vivo estrogenic assays or in vitro estrogen receptor assays, estrogenic activity was not observed. Since APs have been shown to alter activity and content of cytochrome P450s (CYP) which convert diuron to potential estrogenic metabolites, the hepatic biotransformation of diuron was measured with and without a 7 day pretreatment of p-Octylphenol (OP) and p-Nonylphenol (NP) at low (OP 13 ng/L + NP 91 ng/L), and high concentrations (OP 65 ng/L + NP 455 ng/L) in juvenile male Nile tilapia (Oreochromus niloticus). Pre-treatment with the OP/NP (AP) mixture caused elevated levels of NADPH-catalyzed formation of 3,4-dichlorophenyl-N-methylurea (DCPMU) but not 3,4-dichlorophenylurea (DCPU). Fish were also treated with nominal concentrations of low (40 ng/L) and high (200 ng/L) diuron and each of its three degradates/metabolites: DCPMU, DCPU and 3,4-dichloroaniline (DCA). Additional treatments were conducted with APs and Diuron as a mixture at the low concentrations which mimicked concentrations observed in surface waters. Hepatic vitellogenin (Vtg) mRNA was induced by exposure to the high concentrations of Diuron, as well as DCPMU and DCPU in both concentrations. Brain cytochrome P450 aromatase activity was generally diminished by diuron, its metabolites, and the AP/diuron mixtures. 17β-Hydroxysteroid dehydrogenase (17βHSD) levels were also reduced by DCPMU and DCA in the lower concentrations, but not by higher concentrations. While the AP mixture reduced 17βHSD, the AP/diuron mixture induced testosterone (T) biosynthesis at the single concentration tested. Although CYP3A expression was induced by all diuron metabolites, it was unchanged by the AP mixture. These data indicate that mixtures of AP and diuron enhanced the formation of the metabolite (DCPMU) which induced vitellogenin, and reduced T biosynthetic enzymes (17βHSD inhibition). Overall, these data showed that APs may have induced the biotransformation of diuron to at least one metabolite, that may disrupt androgen biosynthesis and potentially alter steroid feedback pathways in the central nervous system.
Keywords: Alkylphenols; Anti-androgen; Biotransformation; Cytochrome P450; Diuron; Vitellogenin